Design and implementation of ultra high frequency 921 MHz reader antenna for indoor propagation / Syamimi Mohd Norzeli - Mohd Norzeli, Syamimi (Institute of Graduate Studies, UiTM, 2018)
In recent years, Radio Frequency Identification (RFID) technology is highly demanded in various applications, requiring a rapid development in the RFID technology. The Ultra High Frequency (UHF) RFID reader was selected for this research due to its further detection distance compared to the High Frequency (HF) and Low Frequency (LF). The research described in this thesis focuses on the development of the UHF RFID reader microstrip antenna designs to meet the requirements of certain applications which are long read range detection and in a small area. The proposed reader antenna has a unique and innovative design as it uses a combination of circular polarized technique, array, parasitic elements and complementary split ring resonator (CSRR) in order to increase gain and miniaturized the reader antenna. In this project, four designs of UHF-RFID reader antenna were proposed namely an UHF reader antenna (UHF-RA), an UHF reader array antenna (UHF-RAA), an UHF reader parasitic array antenna (UHF-RPAA), and miniaturized UHF reader parasitic array antenna (UHF-MRPAA). In the UHF-RA configuration, the behaviour of the circular polarized technique of single element was investigated. The objectives and target of this structure were to prove that the circular polarized method are achieved. At this stage, the design focused on the effects of the truncated patch at the corner to achieved the circular polarized reader antenna. Meanwhile, once the design of circular polarized reader antenna have been proven, the same antenna was upgrade to a 2 x 2 array structure known as UHF reader array antenna (UHF- RAA) in order to increase the gain…